An algorithm for obstacle‐avoiding clock routing tree construction with multiple TSVs on a 3D IC. Issue 2 (27th November 2018) - Mondal, Khokan; Chatterjee, Subhajit; Samanta, Tuhina
Abstract : Effective clock tree design is an important factor for determining chip performance. In this study, the authors present a 3D clock tree design algorithm to enhance the speed and performance of a VLSI chip. The authors propose an algorithm to determine the performance of the clock network by optimising both the clock skew and the dynamic power consumption of the 3D IC clock tree. The authors propose an algorithm for clock tree design based on the Elmore Delay method and routes all the sinks efficiently considering the obstacles with the use of an optimum number of through‐silicon‐vias (TSVs). The proposed method starts with a segregation technique to divide the sinks into smaller zones. Subsequently, an obstacle avoiding abstract clock tree is constructed with a minimum number of TSVs and buffers. The skew and dynamic power of the tree is calculated. Consequently, the proposed method is compared with recent existing works. The experimental results so obtained are quite encouraging.